Adenosine diphosphate-induced platelet aggregation is associated with P2Y12 gene sequence variations in healthy subjects - FONTANA, Pierre; DUPONT, Annabelle; GANDRILLE, Sophie; BACHELOT-LOZA, Christilla; RENY, Jean-Luc; AIACH, Martine; GAUSSEM, Pascale (Circulation (New York, N.Y.), 2003)
The adenosine diphosphate (ADP) receptor P2Y12 plays a pivotal role in platelet aggregation, as demonstrated by the benefit conferred by its blockade in patients with cardiovascular disease. Some studies have shown interindividual differences in ADP-induced platelet aggregation responses ex vivo, but the mechanisms underlying this variability are unknown. We examined ADP-induced platelet aggregation responses in 98 healthy volunteers, and we identified 2 phenotypic groups of subjects with high and low responsiveness to 2 micromol/L ADP. This prompted us to screen the recently identified Gi-coupled ADP receptor gene P2Y12 for sequence variations. Among the 5 frequent polymorphisms thus identified, 4 were in total linkage disequilibrium, determining haplotypes H1 and H2, with respective allelic frequencies of 0.86 and 0.14. The number of H2 alleles was associated with the maximal aggregation response to ADP in the overall study population (P=0.007). Downregulation of the platelet cAMP concentration by ADP was more marked in 10 selected H2 carriers than in 10 noncarriers. In healthy subjects, ADP-induced platelet aggregation is associated with a haplotype of the P2Y12 receptor gene. Given the crucial role of the P2Y12 receptor in platelet functions, carriers of the H2 haplotype may have an increased risk of atherothrombosis and/or a lesser clinical response to drugs inhibiting platelet function.